The influence of cannabis motives on alcohol, cannabis, and tobacco use among treatment-seeking cigarette smokers - Foster, Dawn W. (Drug Alcohol Depend, 2014)
OBJECTIVES: The present study evaluated the effects of cannabis motives on multi-substance use in an effort to examine the incremental validity of cannabis motives with respect to substance use outcomes. METHODS: Participants were 167 treatment-seeking smokers (41.92% female; M(age) = 28.74; SD = 11.88) who reported smoking an average of 10 or more cigarettes daily for at least one year. RESULTS: Structural equation modeling was used to examine the association between cannabis motives and two dependent variables each for alcohol (drinking frequency and alcohol problems), cannabis (cannabis use frequency and cannabis problems), and tobacco (average cigarettes per day and nicotine dependence). Findings indicated that conformity motives were linked with increases in alcohol problems and cannabis problems. Enhancement motives were associated with increased cannabis use and cannabis problems. Coping motives were linked with increased cannabis use and cannabis problems. Contrary to expectations, expansion motives were associated with reductions in the number of cigarettes smoked per day. Also, results supported expectations that the observed effects due to cannabis motives were unique from shared variance with theoretically relevant covariates. CONCLUSIONS: The present findings supported predictions that cannabis motives would evince effects on the use of multiple substances over and above theoretically relevant variables. However, results indicate that the relationship between cannabis motives and multi-substance use is complex, and therefore, additional research is warranted to better understand substance use intervention.